(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article is devoted to the pedagogical conditions of managing the professional competence of future teachers. This article provides examples of the pedagogical conditions necessary for the professional development and supervision of future teachers in the educational process. And also the built model of realization of pedagogical conditions of formation of professional competence of the teacher in educational process is based on target, emotional-motivational, meaningful, operative-activity, control-assessment, effective-interdependence. Accordingly, the dominant set of conditions in the model is characterized by components: loss of selfawareness and self-identification to the individual subject; creative work; otherwise take advantage; dialogizing the learning process.